The Incidence Rate of Echinococcosis in Uzbekistan. - Shavkat Avazimbetov; Sardor Sulaimonov; Begzod Sultonov (American Journal of Biology and Natural Sciences, 2025)
these products quality are varying. Today quality control of meat and meat products is very important in slaughterhouses in terms of safety. The conducted studies of the meat of healthy and echinococcosis animals allow us to conclude that this disease has some influence on some parameters that determine the quality of meat. According to a study of 1679 cattle slaughtered in slaughterhouses in the Samarkand region of Uzbekistan, the average incidence of